Penerapan Data Mining Untuk Memprediksi Tingkat Kemampuan Anak Dalam Mengikuti Mata Pelajaran Dengan Metode C4.5 Pada SDN 105351 Bakaran Batu - Aprianto Tumanggor; Penda Sudiarto Hasugian (Program Studi Teknik Komputer, Fakultas Teknik. Universitas Serambi Mekkah, 2021)
The development of very advanced technology can help all aspects of life, one of which is in the world of education. The world of education certainly really needs the role of technology in managing activities by utilizing information technology. The problem that arises is the system for processing piles of data in order to know whether or not the student is able to follow the subjects at SDN 105351 Bakaran Batu. The process of implementing this data mining application only discusses predicting children's ability levels in following subjects. The data used were data from grade 5 elementary school students from the last 2 years (2018-2019) at SDN 105351 Bakaran Batu. One of the classification models is making a decision tree. By knowing the level of ability of children in following student subjects is expected to provide solutions for the future in processing student data with a computerized system, especially data regarding the level of children's ability in following subjects. The way the system works is built using the C4.5 method and data mining applications that will be designed with VB Net and Microsoft Access databases.